Role Effectiveness Bhabinkamtibmas In Effort To Prevent And Eradicate Criminal Acts Of Domestic Violence - Teguh Wibowo; Siti Ummu Adillah (Universitas Islam Sultan Agung, 2021)
This writing aims to find out and analyze the effectiveness of role Bhabinkamtibmas in preventing cases of domestic violence in rural areas. The type of research used in this study is a type of legal research juridic-sociological. The approach uses sociological juridical. In principle, the duties of the police universally are to protect (protections), provide services to the community (services), enforce the law and maintain order (law enforcement and maintain law and order). Including roles of Bhabinkamtibmas in preventing and reducing the number of domestic violence in rural areas, the existence of various problems and weaknesses in the form of the lack of facilities and infrastructure as well as community culture make the role of Bhabinkamtibmas in preventing and reducing the number of domestic violence in rural areas has not been effective, one of which is shown in the Grobogan area, especially in the Keradenan area, where domestic violence is dominated by physical violence. So it is necessary to involve the community and increase information facilities and infrastructure through the use of digitalization related to the presence of Domestic Violence in rural areas. This can be seen in prevention of cases of Domestic Violence in rural areas in Grobogan is still quite high, this view is shown by the fact that there have been 20 cases of Domestic Violence in the Grobogan area, 11 cases occurred in Keradenan Village, Grobogan Regency where physical violence dominates.